Effect of glutenin subunits on the baking quality of Brazilian wheat genotypes - Costa, Mariana Souza [UNESP]; Santos Scholz, Maria Brigida dos; Miranda, Martha Zavariz; Landi Franco, Celia Maria [UNESP] (Inst Agronomico, 2017)
This study aimed to evaluate the effect of the high and low molecular weight glutenin subunits on the grain traits of sixteen Brazilian wheat genotypes. Grain hardness index, milling traits, physicochemical and rheological properties of the flour, and specific volume and firmness of the bread were evaluated. Physicochemical properties of the flour were not influenced by glutenin subunits. Genotypes with subunits at the Glu-B1 (17+18 or 7+8), Glu-D1 (5+10), and Glu-A3 (b) were associated with strong flours and bread with high specific volume and low firmness. The subunits at the Glu-A1 and Glu-B3 had no effect on the rheological properties of the dough and bread quality, while the subunit 2+12 at Glu-D1 negatively affected the resistance to extension, and specific volume and firmness of the bread. Specific volume and firmness of the bread were influenced by the rheological properties of the dough, while the flour protein content was not important to define wheat quality. The identification of glutenin subunits at different loci along with the rheological tests of the flour are fundamental in estimating the potential use of different materials developed in wheat breeding.
Keywords: high and low molecular weight glutenin subunits; rheology; baking